Pengaruh Customer Experience Terhadap Keputusan Pembelian Produk Karung Goni Dan Kotak - Aubrey Wijaya; William Vincent; Mangihut Tampubolon (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to find the influence of customer experience on purchasing decisions for PT sack and box products. Prima Lestari Image. The method used in this research is a quantitative descriptive technique which explains the data description of the influence of customer experience variables on purchasing decisions, using observation guidelines, questionnaires and literature studies. The questionnaire used in this research was written and intended to be filled in by 50 respondents who are partner companies of PT. Prima Lestari Image. The questionnaire was administered based on the principle of saturated sampling where the entire population was taken to be used as a sample. This research uses a partial test and also a coefficient of determination test to find the existence of an influence and also the magnitude of the influence exerted. The results of research on these two variables have shown that there is an influence between customer experience on PT purchasing decisions. Prima Lestari Image. This influence is explained by the customer experience t-value of 1.711 > ttable value of 1.677. The magnitude of the influence of customer experience on purchasing decisions is 31.4%, so the remaining amount of 68.6% is considered as variables that are not included in this research, such as word of mouth, electronic marketing and others.